Is content marketing still possible? - Toms, Justine (Media and Language, 2024)
Today, we create more content than ever, driven by technology that makes it easy to produce and share images, videos, and text. With this surge in content creation, society is overwhelmed by information, from essential news to trivial updates. This overload diminishes our ability to focus, think critically, and discern valuable content from noise.Now, with “me-media,” everyone creates and consumes content, often without clear purpose, leading to a content glut. Businesses struggle to stand out, as quantity eclipses quality. This overproduction of content makes it difficult for people to distinguish between meaningful and shallow information. Content creators often produce “filler” with little real value. In today’s attention economy, even high-quality content struggles to be noticed.For marketers, content is a powerful tool, but they face new challenges. Companies must offer education, inspiration, and engagement to capture attention. In this crowded space, well-told stories across multiple formats remain essential for connecting with audiences.
Keywords: content; digital content; keywords; attention; artificial intelligence; creative content; digital space; audience